Peletakan Dapur: Bentuk Ketertiban dalam Ketidakteraturan pada Kampung Kota - Farrah Eriska Putri; Adinda Christina (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
In general, informal settlements in Urban Kampung often went through adaptations and changes to accommodate the activities of their residents. The residents in informal settlements naturally change or add spaces to their dwellings without any binding rules, this often creates disorder and chaos in the spatial arrangement. In the case of Kampung Muka, this kind of independent space adaptation also occurs. However, in several cases, such as the placement and addition of service area, a consistent trend was found in the pattern of spatial adaptation. The residents seem to have their own rules in arranging service area, such as the kitchen on the outside of their dwelling. The existence of rules or agreements that appear in this community is very interesting, considering that informal communities tend to be considered exempt from rules. Understanding the emergence of rules that bind spatial adaptation then becomes important to see how far the limits and flexibility can be applied to densely populated housing especially to residents from informal environments. This study uses qualitative data collection methods in the form of observations of the spatial placement of spaces and activities, as well as in-depth interviews with respondents. In the end, the study succeeded in identifying how the kitchen as a form of spatial adaptation and the implied rules that accompany it.